The Impact of Public Service Quality and Facilities on Community Satisfaction in BAPPENDA City Cimahi services - Ayi Muhiban; Anggita Titania (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted in BAPPENDA Cimahi City. The purpose of this study was to examine the extent to which the impact of quality of public services and facilities contributes partially or simultaneously to community satisfaction with services in BAPPENDA Cimahi City. Descriptive and associative methods are used as research methods. The survey sample consists of 100 of his respondents. A random sampling method is used for the sampling method. The analysis method uses multiple regression analysis. Research results show that the quality of public services and public facilities partially and simultaneously affects public satisfaction. The study concludes that officials can improve the quality of public services through a more effective and efficient system, improve the facilities provided, and enhance the aspects of the community that can provide an unforgettable experience. It is expected that this will increase the satisfaction of employees